Efektifitas Neuromuscular Taping (NMT) sebagai Terapi Non-Farmakologi pada Penderita Carpal Tunnel Syndrome di RS Saiful Anwar, Malang: Sebuah Laporan Kasus - Setianto, Catur; Rahmy, Septy; Sudjatmoko, Azhar (RSUD Dr. Saiful Anwar Province of East Java, 2021)
Introduction: Carpal Tunnel Syndrome (CTS) is a peripheral nerve lesion that is often encountered due to non-traumatic mechanisms. There are various methods of CTS therapy to reduce complaints and increase patient productivity. One of the non-pharmacological methods that can be used is Neuromuscular Tapping (NMT). The purpose of this case report is to determine the effectiveness of using NMT as a non-pharmacological therapy in CTS patients who have previously received pharmacological therapy, measured by the NRS (Numeric Pain Rating Scale) in patients. Case Illustration: A 52-year-old woman came with complaints of tingling in the right and left wrists for four months with a history of working in cigarette factory for ten years. Physical examination revealed pain in the right and left wrists with NRS 6-7, hypesthesia in fingers 1, 2, 3, and ½ 4 of volar manus bilaterally; the patient has taken antiinflammatory drugs, and the pain improves when taking the drug but will relapse when not taking medication. The patient was diagnosed with Carpal Tunnel Syndrome bilateral (Rosenbaum level 2/ persistent symptoms); the patient received pharmacological therapy by administering NSAIDs (Nonsteroidal Anti-Inflammatory Drugs) and corticosteroid injections but did not show any improvement in pain, then the patient underwent NMT as non-pharmacology therapy. Discussion: In the results of the patient's follow-up after undergoing NMT therapy, there was an improvement in the patient's complaints, as seen from the improvement in the patient's NRS score.